2010
DOI: 10.1177/0009922809359418
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the “Tipping Point” Age for Overweight Pediatric Patients

Abstract: According to the National Health and Nutrition Examination Survey in 2007, nearly half of all American children are either overweight or obese. Retrospective chart review identified patients with the diagnostic codes for overweight, obese, and/or excessive weight gain. Inclusion criteria were current age between 2 and 20 years, a minimum of 5 visits with weight and height measurements, and a body mass index (BMI) at or above the 85th percentile. A total of 184 patients met inclusion criteria. More than half th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 29 publications
2
44
0
3
Order By: Relevance
“…Overweight during childhood has both immediate and longer term health effects, including an increase in the prevalence of early cardiovascular disease and diabetes (Pinhas-Hamiel et al, 1996;Freedman et al, 1999). Programs to address obesity are a high priority for public policy (Gill et al, 2009) especially for young children (Harrington et al, 2010). Research into dietary determinants of obesity is challenging because diets are complex, and both diet and energy expenditure influence weight status.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight during childhood has both immediate and longer term health effects, including an increase in the prevalence of early cardiovascular disease and diabetes (Pinhas-Hamiel et al, 1996;Freedman et al, 1999). Programs to address obesity are a high priority for public policy (Gill et al, 2009) especially for young children (Harrington et al, 2010). Research into dietary determinants of obesity is challenging because diets are complex, and both diet and energy expenditure influence weight status.…”
Section: Introductionmentioning
confidence: 99%
“…For example, formula-fed infants have fat deposition and increased number of adipocytes through a greater insulin response compared to those breast-fed 1,29 . In addition, displacement of breast milk containing low protein by earlier introduction of CF including higher energy and protein 30 may lead to high energy 31 and protein intake 32 in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity starts early and tends to persist into childhood and adulthood 1 . Research has therefore focused on identifying the factors attributable to the development of obesity with emphasis on the first year of life as a critical period to target 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is considered to be one of the obesity-related diseases; type 2 diabetes in children has linked with obesity; when the pancreas starts to produce the insulin hormone, excess body fat will not allow child's body to use the insulin as it should be which can lead to being a diabetic patient. [6] Parents should also be aware of the social contexts in which foods are consumed, studies have demonstrated that children develop preferences for foods offered in positive contexts and conversely, are more likely to dislike foods offered in negative contexts. [7] Parents should encourage healthful eating habits at home by making healthful foods available, increasing the number of family meals eaten together, and reducing the availability of sugarsweetened beverages and sodas.…”
Section: Introductionmentioning
confidence: 99%